Driving Strategic Capability based on Artificial Intelligence Literacy: The Mediating Role of Employee Agility in AI-Enabled Organizations - Pranaputra, Randy Dwi; Suryadi, Edi; Disman, Disman; Askolani, Askolani (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid diffusion of artificial intelligence (AI) across organizational functions has shifted strategic attention from mere technological adoption toward the development of human-centered capabilities. Strategic capability is operationalized through organizational responsiveness and strategic alignment in leveraging AI. Data were collected from 350 employees working in AI-adopting organizations in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model demonstrates satisfactory reliability and validity. Structural model results indicate that artificial intelligence literacy has a significant positive effect on employee agility (β = 0.62, p < 0.001), and employee agility significantly enhances strategic capability (β = 0.67, p < 0.001). Mediation analysis confirms a significant indirect effect of artificial intelligence literacy on strategic capability through employee agility (β = 0.41, p < 0.001), with a variance accounted for (VAF) of 66 percent, indicating partial mediation. These findings suggest that artificial intelligence literacy alone is insufficient to generate strategic advantage unless activated through agile employee behavior. The study contributes theoretically by identifying employee agility as a key microfoundation linking AI literacy to strategic capability. Practically, the results highlight the importance of integrating AI literacy development with agility-oriented human resource practices to support sustainable competitiveness, aligning with SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure). Keywords: Artificial intelligence literacy, employee agility, strategic capability, PLS-SEM